Forming of Professional Competences by Means of Developing Abilities and Skills as a Pedagogical Problem - Iryna Kustovskaya (Pedagogical Discourse, 2012)
The article deals with the analysis of interrelations between professional competences and professional skills which are the main in forming future economists. The author classifies professional competences according to the level of their influence on the process of development of future specialist and defines the main pedagogical approaches to the forming of abilities and skills.